Correlation analysis of serum PAPP-A2, PIGF with the prognosis of gestational diabetes mellitus: Serum PAPP-A2, PIGF with the prognosis of gestational diabetes mellitus - Gao, Mengjie; Sheng, Xiaomei; Wang, Mengni; Gu, Xiaoxia; Yu, Hong; Huang, Tiantian; Zhang, Ling; Wu, Li; Gui, Yadi (Journal of Medical Biochemistry, 2026)
[Objective] To assess the diagnostic efficacy of the detection of serum Pregnancy-Associated Plasma Protein A2 (PAPP-A2), placental growth factor (PIGF), and secretory crimp-associated protein 5 (SFRP5) for detrimental effects of gestational diabetes mellitus (GDM) on pregnant patients.[Methods] 242 patients who received a GDM diagnosis at this hospital between January 2023 and December 2024 were chosen to be the GDM group. The normal pregnancy group consisted of 156 healthy expectant mothers who received prenatal care at this hospital over the same time frame. Patients in the GDM group were divided into the well-controlled diabetes group, the poorly controlled diabetes group and the high-risk group according to the level of glycated hemoglobin (HbA1c). Based on their follow-up results, patients in the GDM group were split into two groups: those with poor pregnancy outcomes and those with favorable pregnancy outcomes. Serum PAPP-A2, PIGF, Adipokine SFRP5, and urine microalbumin (mAlb) levels varied between the GDM and normal pregnancy groups. Univariate and multivariate analyses were used to analyze the factors influencing pregnancy outcomes and the relationships between the levels of serum PAPP-A2, PIGF, Adipokine SFRP5 and urine mAlb and the degree of blood glucose control and adverse pregnancy outcomes. In addition, it has diagnostic efficacy for adverse pregnancy outcomes in patients with GDM.[Results] Serum PAPP-A2, PIGF, and Adipokine SFRP5 levels were considerably lower in the GDM group than in the group with a normal pregnancy (P
Keywords: Placental growth factor; Secretory coil-associated protein 5; Gestational diabetes; Adverse pregnancy outcomes; Pregnancy-Associated Plasma Protein A2